National Survey of Pharmacy Leadership at Ministry of Health in Saudi Arabia: Planning and Organization - Alomi, Yousef Ahmed; Abdulmohsen Albaz, Modhi; AlMuhraj, Wejdan Fawzan; AlKharji, Mashael Yasser; Alshuraym, Norah Rushud (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the national survey of pharmacy leadership at the Ministry of Health with emphasis on pharmacy planning and organization. Methods: It is a ninety days cross-sectional national survey of pharmacy leadership practice at Ministry of Health. The survey modified from self-assessment of 360 leadership and with pharmacy leadership literature. It consisted of a demographic section, leadership pathway, and fifty-three leadership ship questions. It contained selected eighteen leadership skills of 360 leadership self-assessment. The electronic format of the survey through the survey monkey system and distributed through emails. All analysis is done through the survey monkey system. The survey divided into for several parts for analysis, and discussion. Part one: practice management, part two: planning and organizations, part three: communications strategies, part four: problem-solving and decision making, part five: performances management, part six; working environment, and part seven: professional development. The study explored the part number two; National Survey of Pharmacy leadership: planning and organizations. Results: The survey distributed to one hundred hospitals, the response rate, was forty-two hospitals (42%) with seventy-pharmacy leaders. The gender distribution of responders was Male 43 (63.24%) and female 25 (36.76%) while the nationality was Saudi 69 (98.57%) and non-Saudi 1 (1.43%). The majority of responders were in the age range (25-34) years 30 (55.12%) and (35-44 years) 26 (38.24%). The average score planning skills (achievement) was 2.41 (80.33%) with the highest score was Makes a plan was done and translate strategic action 2.48 (82.65%), and the lowest score was Completes work on given time frame and budget 2.35 (78.32 %). The average score planning skills (Goals) was 2.61 (86.99 %) with the highest score was Makes sure that I have a bright idea of our group’s goals 2.74 (91.32%), and the lowest score was Achieves goals Successfully 2.44 (81.32%). The average score organization skills (Flexibility) was 2.58 (85.99%) with the highest score was Adapts to new organizational structures, policies, or procedures 2.67 (82.65%), and the lowest score was Can handle changes without complaining 2.37 (78.99%). Conclusion: The pharmacy leaders had excellent planning skills and organization with the inadequacy of objective achieving with appropriate time or budget. The regular survey of pharmacy leadership every one or two years is highly recommended for all healthcare organization in the kingdom of Saudi Arabia.
Keywords: Pharmacy leadership; Planning; Organization; Ministry of health; Saudi arabia